(untitled) (Research, Society and Development, 2022)
Objective: To carry out a theoretical reflection on how epidemiological data interrelate with the historical recovery of patient safety, and also to reflect on how Nursing care in the Intensive Care Unit is a protagonist in direct actions to reduce adverse events. Methodology: This is a descriptive study of the reflective analysis type, which is systematized in two stages: a narrative review that enabled the theoretical and conceptual development of the theme and subsequent analysis between adjacent concepts. Results: From the theoretical development, it was verified the need to improve the understanding of the context in which people are harmed during health care, in order to direct public policies aimed at the quality of services. In the subsequent analysis, the study of adverse events imposes the importance of risk indicators, as they allow measuring the gap between the assistance provided and the ideal care, providing indispensable information for the construction of a safer health system. Therefore, the establishment of the six international goals in the World Alliance for Patient Safety, allows to improve care in areas assessed as being at greatest risk. Final Considerations: Thus, for hospital administration, above all in the Intensive Care Unit, a review of adverse events is an essential strategy for good risk management, as it offers a reduction in incidents, a reduction in losses and costs inherent to adverse events, facilitating decision-making and planning, and helping to improve patient safety.